THE EFFECT OF INDIRECT CODED FEEDBACK ON STUDENTS’ WRITING ABILITY - Sri Nurhayati (OKARA: Jurnal Bahasa dan Sastra, 2017)
The purpose of this research is to know whether indirect coded feedback gives a better effect on students’ writing ability rather than direct feedback. the design used in this experimental research was randomized group post test only design. The researcher did lottery to every student to divide them into A and B class. Then the experimental group and the control group were randomly chosen by a flip coin. A class or the experimental group was given correction by using codes on the errors they made in their first draft or indirect coded feedback, while B class or control group was given the correct form of the errors or direct feedback on their first draft. The treatments were done three times and the result of post-test then was analyzed. The result of the data analysis that gotten from the statistical computation of the post test result showed that the t-value was higher than that of t-table. This indicated that students who got indirect coded feedback have better writing ability than the students who got direct feedback on their writing.